A carpet cloak based on gradient metasurfaces. (April 2019) - Wang, R; Yue, S; Hou, Y; Liu, S; Li, M; Zhang, Z
Abstract: In this paper, we numerically demonstrate a carpet cloak operating in reflection with the incident wavelength of 800 nm. The carpet cloak comprises gradient metasurfaces with a metal-insulator-metal configuration. The gradient metasurfaces reroute the indicent light and restore the reflectted wavefront by compensating the phase differences between each unit cell of the metasurface. The proposed cloak is ultrathin, simple and easy for practical implementation.